Материальная система CdTe–ZnTe–HgTe: анализ смешиваемости твердых растворов - Гамбарян, К. М.; Симонян, А. К.; Арутюнян, В. М.; Гамбарян, М. К. (Հայաստանի ԳԱԱ)
Исследованы псевдобинарные системы HgTe–CdTe, ZnTe–CdTe и HgTe–ZnTe и определены энергии смешения Гиббса в интервале температур 400–1000 К. Анализ области смешиваемости для четырехкомпонентного твердого раствора CdZnHgTe также осуществлен с помощью расчета свободной энергии Гиббса. Ուսումնասիրվել են HgTe-CdTe, ZnTe-CdTe և HgTe-ZnTe քվազիերկբաղադրիչ նյութական համակարգերը և որոշվել է դրանց խառնման Գիբսի էներգիաները 400– 1000 Կ ջերմաստիճանային տիրույթում: Գիբսի ազատ էներգիան հաշվարկելու միջոցով նաև վերլուծվել է քառաբաղադրիչ CdZnHgTe պինդ լուծույթի անհամատեղելիության գոտիները: The pseudobinary HgTe–CdTe, ZnTe–CdTe and HgTe–ZnTe systems were studied and Gibbs energy of mixing were determined at 400–1000 K temperature range. Miscibility gap analysis for CdZnHgTe quaternary material system is also performed by the Gibbs free energy calculations. Quantitative explorations show that there is no immiscibility gap for CdTe–HgTe material system in the mentioned above temperature range․
Keywords: Physics